The role of red blood cell distribution width in predicting coronary artery lesions in pediatric patients with kawasaki disease - Cai, Jianghui; Tang, Mi; Shuai, Shuping; Zhang, Rui; Zhang, Hongxi; Yang, Yanfeng; Wu, MengJun; Liang, Hua; Xing, Shasha (Frontiers in Cardiovascular Medicine, 2023)
Background: Recent studies have shown that red blood cell distribution width (RDW) has emerged as a novel predictor of cardiovascular diseases. We aim to investigate the association between RDW and the risk of coronary artery lesions (CALs) in pediatric patients with Kawasaki disease (KD). Methods: KD patients were classified as the CALs group (patients with CALs) and non-CALs group (patients without CALs). Differences among the groups were analyzed by Mann–Whitney U-test and Chi-square analysis. The independent risk factors of CALs were identified by multivariate logistic regression analysis, followed by receiver operating characteristic (ROC) curve analysis to calculate the optimal cut-off value. Results: The levels of red blood cell distribution width (RDW) and C-reactive protein were significantly higher in the CALs group than those in the non-CALs group (p<0.01). Further multivariate logistic regression analysis revealed that RDW (OR=5.2, 95% CI, 4.064 to 6.654) and incomplete KD were independent risk factors of CALs in KD patients (p<0.01). According to the ROC analysis, the optimal cut-off value of RDW for predicting CALs was >13.86 %, with a sensitivity of 75.79% and specificity of 92.81% (area under curve = 0.869, 95% confidence interval = 0.844-0.892; p<0.0001). Conclusions: RDW is an independent predictor with high sensitivity and specificity to predict CALs in KD patients. The elevation in RDW level (>13.86 %) may be used as novel biomarkers for early predicting CALs in KD patients during the acute phase.